2015
DOI: 10.1097/mao.0000000000000544
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Saccular Function and Gait Speed

Abstract: Objective To investigate the association between otolith function and age-related gait impairment. Study design Cross-sectional analysis within the Baltimore Longitudinal Study of Aging (BLSA), a longitudinal prospective cohort study. Setting Vestibular testing and gait laboratory within an acute care teaching hospital. Patients Community-dwelling participants, who did not use assistive devices. Intervention(s) Cervical and ocular vestibular-evoked myogenic potentials (VEMPs) as measures of saccular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…First, we found that difficulty walking was universally reported by the older participants in the study. The current literature on vestibular function and walking is relatively sparse, with small studies showing an association between vestibular loss and slower gait speeds and between vestibular loss and shorter step lengths [5, 6]. A more comprehensive understanding of the link between vestibular impairment and gait speed and variability in older individuals is warranted, given the universality of this symptom.…”
Section: Discussionmentioning
confidence: 99%
“…First, we found that difficulty walking was universally reported by the older participants in the study. The current literature on vestibular function and walking is relatively sparse, with small studies showing an association between vestibular loss and slower gait speeds and between vestibular loss and shorter step lengths [5, 6]. A more comprehensive understanding of the link between vestibular impairment and gait speed and variability in older individuals is warranted, given the universality of this symptom.…”
Section: Discussionmentioning
confidence: 99%
“…This increase has been reported for click and tone burst stimulations ( 12 ). Though the majority of studies report no significant effect of age on cVEMP latencies ( 19 , 31 , 33 , 35 ), few authors have observed age-related increased latency on the p13 ( 15 , 34 ) and n23 ( 9 ), while other have reported age-related decreases to n23 ( 24 ). cVEMP response rates are widely reported to decrease with age.…”
Section: Effects Of Aging and Vestibular Evaluation Techniquesmentioning
confidence: 95%
“…Numerous studies have reported a decrease in oVEMP amplitude related to age ( 19 , 29 , 31 , 33 , 35 37 ). More specifically, oVEMP amplitude has been reported to decrease by 2.9 μV per decade, independent of the stimulus used ( 19 , 29 , 31 , 33 , 36 , 37 ). Normal aging has been reported to increase oVEMP thresholds ( 12 ).…”
Section: Effects Of Aging and Vestibular Evaluation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…23 We also previously reported an association between saccular dysfunction and slower walking speed among older women, but not older men. 24 The peripheral vestibular system senses head movements and responds to high-frequency head oscillations that occur during walking. 2526 Vestibular information is also used to stabilize the head and trunk and serves both a postural and gaze stability purpose.…”
Section: Discussionmentioning
confidence: 99%